HEPATITIS E SEROPREVALENCE AND SOCIODEMOGRAPHIC CHARACTERISTICS AT A TERTIARY CARE HOSPITAL - Wankhede, Sandeep (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Enterically transmitted hepatitis is frequently caused by the hepatitis E virus, which is spread by tainted food and water. Globally, there are regional, population, and circulating HEV genotype differences in the prevalence rates of antibodies to the hepatitis E virus (anti-HEV), with unexpectedly high seropositivity in some developed settings. Aims & objectives: The purpose of the current study was to examine the sociodemographic characteristics and seroprevalence of Hepatitis E infection at a tertiary hospital. Material and Methods: Informed consent was obtained before the current single-center, prospective, observational study was conducted on patients with clinically suspected acute viral hepatitis who were willing to participate. IgM anti-HEV was found using the RecombiLISA test in human serum or plasma. Results: Anti-HEV testing revealed 72 (10.29%) reactive cases. The age groups of 31-45 years (13.27%) and 15-30 years (12.2%) had the highest rates of anti-HEV test reactivity, whereas the age groups of 41-60 years and 15 years exhibited, respectively, 4.17% and 3.28%. There was no statistically significant relationship between the anti-HEV test and the various age groups. (P = 0.0187) Male cases of HEV positivity outnumbered female cases by a larger margin (15.38%). The difference was statistically significant (5.52%). (p value – 0.002). The ratio of men to women was 2.6:1. Among hepatitis E cases, the mean values for total bilirubin, SGOT/AST, SGPT, ALP, and A/G ratio were 3.35 ±2.45, 138.28 ±19.35, 408 ±106, 1516 ±447, and 0.32 ±0.14, respectively. The months of July and August saw the highest number of hepatitis E cases (42 and 14, respectively), with September, November, and December each seeing two cases. Seropositive cases and months correlated in a statistically significant way. Conclusion: Adults and older children were found to have higher HEV incidences. Timely diagnosis by serology and PCR, in addition to assistance from clinical diagnosis and biochemical analysis, may help in early management and prevention of complications. Keywords: HEV infections, acute viral hepatitis, sociodemographic profile, Anti – HEV test